The Influence of Price and Location on Purchasing Decisions at the Mojok Yuk Shop Batununggal Bandung City - Syalwa Rezkia Muhti; r Iim Takwim (Escalate : Economics and Business Journal, 2026)
The culinary industry in Bandung faces intense competition, with Kedai Mojok Yuk Batununggal experiencing declining sales from Rp14,729,000 (May 2025) to Rp11,324,000 (October 2025) due to uncompetitive prices and non-strategic location; this study aims to analyze the partial and simultaneous effects of price and location on purchasing decisions using a quantitative descriptive-verification approach on a population of 2,767 consumers (May-October 2025) with a sample of 96 respondents, employing questionnaires and observations analyzed via classical assumption tests, multiple linear regression (Y=6.953+0.712X1+0.539X2), t-tests, F-tests, and coefficient of determination (adjusted R²=0.753); results show price positively and significantly affects purchasing decisions (t=5.381, p<0.001), location positively and significantly affects purchasing decisions (t=4.474, p<0.001), and both simultaneously significant (F=145.550, p<0.001); thus, price and location are key drivers of purchasing decisions, recommending the shop optimize competitive pricing and location accessibility for sales recovery.